Nanosized Liposomes Containing Bile Salt: A Vesicular Nanocarrier for Enhancing Oral Bioavailability of BCS Class III Drug - Mosab Arafat; Cathrin Kirchhoefer; Momir Mikov; Muhammad Sarfraz; Raimar Löbenberg (Frontiers Media S.A., 2017)
PURPOSE: Liposomes have been studied as a colloidal carrier in drug delivery systems, especially for oral administration. However, their low structural integrity in the gut is still a major shortcoming. Membrane disruptive effects of physiological bile salts in the small intestine result in premature drug release prior to intestinal absorption. Thus, we analyzed the stabilizing effect of sodium deoxycholate when incorporated into nano-sized liposomes. METHOD: Cefotaxime-loaded liposomes were prepared with different sodium deoxycholate concentrations (3.75- 30 mM) by rotary film evaporation followed by nano-size reduction. The physical integrity of liposomes was evaluated by monitoring cefotaxime leakage, particle sizes in different simulated physiological media. The oral bioavailability and pharmacokinetics of cefotaxime was assessed in rats (n = 6 per group) after single dose of drug-encapsulated in liposomes containing bile salt, drug in conventional liposomes, and cefotaxime solution (oral and intravenous). RESULTS: Simulated gastric fluid with low pH showed less effect on the stability of liposomes in comparison to media containing physiological bile salts.  Liposomes containing 15 mM sodium deoxycholate were most stable in size and retained the majority of encapsulated cefotaxime even in fed state of simulated intestinal fluid being the most destructive media. Pharmacokinetics data showed an increase in Cmax and AUC0-inf in the following order: cefotaxime solution < conventional liposomes < liposomes made with bile salts. The total oral bioavailability of cefotaxime in liposomes containing bile salt was found to be 5-times higher compared to cefotaxime solution and twice as much as in conventional liposomes. CONCLUSION: Incorporation of bile salts, initially used as membrane permeation enhancer, also acted as a stabilizer against physiological bile salts. The nano-sized liposomes containing sodium deoxycholate were able to reduce the leakage of encapsulated cefotaxime in the gut due to the improved vesicle stability and to enhance the oral bioavailability of acid-labile drugs up to 5-fold.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.